2005
DOI: 10.1016/j.cell.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Perp Is a p63-Regulated Gene Essential for Epithelial Integrity

Abstract: p63 is a master regulator of stratified epithelial development that is both necessary and sufficient for specifying this multifaceted program. We show here that Perp, a tetraspan membrane protein originally identified as an apoptosis-associated target of the p53 tumor suppressor, is the first direct target of p63 clearly involved in mediating this developmental program in vivo. During embryogenesis, Perp is expressed in an epithelial pattern, and its expression depends on p63. Perp-/- mice die postnatally, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
351
2
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(376 citation statements)
references
References 31 publications
17
351
2
6
Order By: Relevance
“…MFG-E8 might affect these events during carcinoma tissue growth and/or wound healing, since no substantial defect appeared in the corresponding tissues of MFGE8-deficient mice. As reported recently, p63 induces membrane-anchored molecules including the integrin a 3 and b 4 subunits, envoplakin, Perp and bullous pemphigoid antigen-1/2 (Kurata et al, 2004;Ihrie et al, 2005;Osada et al, 2005a, b;Carroll et al, 2006) for cell-cell and cell-matrix binding. Soluble protein MFG-E8 may provide a novel mechanism of epithelialnonepithelial cell interactions around the p63-expressing cells.…”
Section: Mfge8mentioning
confidence: 70%
“…MFG-E8 might affect these events during carcinoma tissue growth and/or wound healing, since no substantial defect appeared in the corresponding tissues of MFGE8-deficient mice. As reported recently, p63 induces membrane-anchored molecules including the integrin a 3 and b 4 subunits, envoplakin, Perp and bullous pemphigoid antigen-1/2 (Kurata et al, 2004;Ihrie et al, 2005;Osada et al, 2005a, b;Carroll et al, 2006) for cell-cell and cell-matrix binding. Soluble protein MFG-E8 may provide a novel mechanism of epithelialnonepithelial cell interactions around the p63-expressing cells.…”
Section: Mfge8mentioning
confidence: 70%
“…Although Perp-deficiency induces completely penetrant lethality on a pure 129/Sv background within the first week of life, a small fraction (B5%) of PerpÀ/À mice survived to adulthood on a mixed 129/Sv;C57BL/6 background. 5 Upon aging these PerpÀ/À mice, we found that they exhibited a significantly decreased lifespan, with a median survival time of only 18 months compared to the survival time of 30 months observed in a wild-type cohort (Figure 2a). PerpÀ/À mice manifested a variety of symptoms prior to death, including decreased weight (31.25% of mice), inflamed skin or rashes (25%, Figure 2b), and fur with a patchy, disorganized or greasy appearance (43.75%, Figure 2b).…”
mentioning
confidence: 83%
“…4 In contrast, Perp expression in unstressed stratified epithelial cells depends on p63, and PerpÀ/À mice die within 10 days after birth due to compromised adhesion and blistering in the oral mucosa and skin. 5 In newborn epithelia, Perp functions in the desmosome, a multiprotein complex required for normal cell-cell adhesion in stratified epithelia. Consistent with a dual role for Perp, experiments in zebrafish have shown that Perp participates in both UV-induced, p53-dependent apoptosis and proper development of the skin and pectoral fins.…”
mentioning
confidence: 99%
“…In stratified epithelia, cells sorted on the basis of high levels of either β1 or α6 integrins appear to have superior clonogenic ability (see below). The transcription factor p63, which transactivates Perp, a protein involved in the assembly of desmosomes, is another factor maintaining the integrity of stratified epithelia [36,37]; Perp-deficient mice suffer severe blistering. p63 has two major isoforms (termed TA and N) that drive at least three transcripts encoding transactivating (TA) and nominally transactivating ( N) isoforms, producing up to six splice variants [38], and it is the TAp63 isoforms that appear to be involved in maintaining cells in an immature state.…”
Section: Self-renewal and The Stem Cell Nichementioning
confidence: 99%